(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2015)
Introduction: Urinary Tract Infection (UTI) is one of the most common bacterial diseases worldwide that can present as asymptomatic or symptomatic characterized by a wide range of symptoms from mild irritative voiding to bacteremia, sepsis or even death. Increase in resistance of urinary pathogens to conventional antimicrobial agents is gaining the attention of many microbiologists worldwide in respect to treatment of urinary tract infection. Since the pattern of bacterial resistance is continuously changing, the monitoring of antibiotic susceptibility pattern becomes more important. Objective: The objective of this study was to update the distribution of current urinary pathogens and to find out their antimicrobial susceptibility pattern. Methods: A Cross sectional descriptive study was conducted at Border Guard Hospital (BGB Hospital) Peelkhana, Dhaka during the period of February 2013 to September 2013. A total of three hundred ninety urine samples were collected from patients with suspected UTI. All the samples were clean catch mid stream urine. Urine samples were cultured on MacConkey agar medium and blood agar medium. Colony counts yielding single type of bacterial growth of 105 CFU/ml were deemed significant. Results: Out of 390 samples, 49(12.56%) samples were culture positive. The isolated organisms were identified by conventional methods and were subjected to determine antimicrobial susceptibility testing by Kirby Bauers disc diffusion method. Escherichia coli (E.coli) was found as the most prevalent isolates 31(63.26%) followed by klebsiella spp 06(12.24%), Enterobacter spp o4(8.17%), Pseudomonas aeruginosa 04(8.17%), Staphylococcus aureus (Staph aureus) 02(4.08%) and Enterococcus spp 02(4.08%). Eight antimicrobial agents namely Amoxycillin, Co-trimoxazole, Levofloxacin, Nitrofurantoin, Gentamicin, Ceftriaxone, Imipenem and Amikacin were used for antimicrobial susceptibility testing. The most effective drug found against urinary isolates was Imipenem (95.91%), followed by Amikacin (81.63%) and Ceftriaxone (69.38%). None of the drug found was 100% effective against urinary pathogens. E.coli was found to be fairly sensitive to Ceftriaxone, Gentamicin and Nitrofurantoin. Conclusion: Urinary tract infection remains one of the most common bacterial infections. Antimicrobial drug resistance is increasing among urinary pathogens. This study updated the current occurrence of urinary pathogens and their antibiotic sensitivity pattern. We recommend periodical determination of antimicrobial sensitivity pattern of urinary pathogens in a particular hospital or area. Journal of Armed Forces Medical College Bangladesh Vol.10(2) 2014